Synergistic Effects of Germination and Ultrasonication on Nutritional and Structural Characteristics of Kodo (Paspalum scrobiculatum) and Little (Panicum sumatrense) Millet - Swarnima Dey; Alok Saxena; Yogesh Kumar; Tanushree Maity; Ayon Tarafdar (Journal of Food Quality)
This study aimed to investigate the nutritional and structural properties of kodo (Paspalum scrobiculatum) and little (Panicum sumatrense) millets on administering ultrasonication and germination treatments. Significant changes in the treated samples were recorded, including lower levels of antinutrients such as tannin and phytates, and higher antioxidant activity, improving their nutritional value. The treated kodo and little millets showed significantly improved nutritional bio-accessibility, with an impressive in vitro protein digestibility of >82%. The modified structure of the starch granules in the treated millets showed pseudoplastic flow characteristics and a polyhedron/spherical morphology which was a novel finding. DSC thermogram revealed that the treated millets may be processed at higher temperatures while exhibiting a lower enthalpy, which could expand their uses in a range of food products. FTIR spectra indicated the presence of phenolic groups in both millet samples studied, at approximately 2817 cm⁻1 frequency. The results obtained offer insightful information about the benefits of ultrasonication and germination for processing kodo and little millets in terms of altered starch characteristics, enhanced bio-accessibility of nutrients, and better nutritional profiles, which qualify millets for the development of functional food products.